Performance enhancement and emissions reduction in a diesel engine using oleander and croton biodiesel doped with graphene nanoparticles - Treza Wambui; Meshack Hawi; Francis Njoka; Joseph Kamau (International Journal of Renewable Energy Development, 2023)
Biodiesel is considered a suitable substitute for petroleum diesel because it is renewable, environment-friendly, and has a low carbon footprint. However, its high density, high viscosity and low heating value prevents it from replacing petroleum diesel completely. This study investigates the performance and emission characteristics of a compression ignition engine operating on oleander and croton biodiesel doped with graphene nanoparticles. Five fuel samples are used, including diesel (D100), diesel - 80% blended with oleander and croton biodiesel - 20% (OCB20) and OCB20 dosed with graphene nanoparticles at mass fractions of 50 ppm (mg/L), 75 ppm (mg/L) and 100 ppm (mg/L), respectively. The chemical composition of biodiesel and graphene nanoparticles is analyzed using Fourier Transform Infrared (FTIR) spectroscopy while the morphology of the nanoparticles is analyzed using Scanning Electron Microscope (SEM). Engine tests reveal a significant improvement in brake thermal efficiency, especially at 75 ppm concentration which is 2.76%  and 18.93% higher than diesel and OCB20, respectively, and a reduction in brake specific fuel consumption by 2.44% and 16.67% compared to diesel and OCB20, respectively. Carbon monoxide (CO) and unburnt hydrocarbon emissions (UHC) decreases for the 50 ppm sample, recording 8.58% and 21.65% reduction in CO and 52.2% and 50% in UHC compared to the diesel and OCB20, respectively. However, Oxides of Nitrogen (NOx) emissions increase. The results indicate that graphene nanoparticle-enhanced biodiesel can adequately substitute petroleum diesel, albeit with NOx reduction techniques.